Effects of Moisture Content in Para Rubber Leaf Litter on Critical Mass Flux and Piloted Ignition Time - Pissanu Wongchai (2018)
© 2015 The Authors. Published by Elsevier Ltd. An attempt has been made to understand the effect of moisture content on the critical mass flux(CMF) and ignition time. It is a key component of understanding fire spread on para rubber plantation in the dry season. The critical mass flux was measured under a variety of external radiant heat flux and moisture content of para rubber leaf litter. From the experiment, the critical mass flux for piloted ignition increased with moisture content. It was found that the critical mass flux was increased 41.36% from moisture content of 0 to 10% and 72.20% from moisture content of 0 to 25%. And it was found that the ignition time for ignition increased by 38.46% and 68.45% for the moisture content increased from 0 - 10% and 0 - 25%, respectively. The same trend was also found for all moisture contents. Therefore the ignition times decreased as heat flux increased.